Enhancing educational influences in learning with a Living Educational Theory approach to pedagogical Action Research in Higher Education. Issue 2 (15th March 2021) - Huxtable, Marie; Whitehead, Jack
ABSTRACT: The last 20 years have seen a growing interest in researching pedagogy in Higher Education with action researchers playing a part in this growth. However, there are few studies that analyse the educational influences in learning of the action researcher in their own pedagogy in Higher Education. Hence the focus of this paper on enhancing educational influences in learning with a Living Theory approach to pedagogical Action Research in Higher Education. This paper presents an analysis of such educational influences. The analysis explains our educational influences in the learning of students who have progressed from the springboard provided by Action Research to recognising and valuing themselves as knowledge creating researchers who are contributing to a global knowledgebase. The analysis draws on data from supervising and tutoring successfully completed masters and doctoral programmes of professional development with teachers and other professional educational-practitioners. The meanings of educational practice, educational influences in learning, educational pedagogy and educational research are clarified. In the discussion we show how a Living Theory approach to pedagogical Action Research in Higher Education enables students to engage in the highest levels of learning, creating, and contributing knowledge with values that carry hope for human flourishing.